2021
DOI: 10.1038/s41419-021-04416-x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-(1,6)-fucosyltransferase (FUT8) affects the survival strategy of osteosarcoma by remodeling TNF/NF-κB2 signaling

Abstract: Glycosylation is an important modification of membrane proteins that results in functional changes in many cellular activities, from cell-cell recognition to regulatory signaling. Fucosyltransferase 8 (FUT8) is the sole enzyme responsible for core fucosylation, and aberrant fucosylation by dysregulated expression of fucosyltransferases is responsible for the growth of various types of carcinomas. However, the function of FUT8 in the progress of osteosarcoma (OS) has not been reported. In this study, we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Consequently, modulation of apoptosis sensitivity during early carcinogenesis might be a viable treatment strategy for CRC that is worthy of investigation to address core fucosylated glycan intermediates involved in apoptosis and drug resistance. In this regard, reduced core fucosylation of TNF receptors may be mechanistically linked to decreased mitochondrial-dependent apoptosis because of the activation of the non-canonical NF-B pathway, as recently reported in osteosarcoma 75 . Therefore, targeting key (1,6)fucosylated proteins could strengthen the panoply of treatment alternatives for CRC and other neoplasias characterised by exacerbated core fucosylation 76,77 .…”
Section: Discussionmentioning
confidence: 52%
“…Consequently, modulation of apoptosis sensitivity during early carcinogenesis might be a viable treatment strategy for CRC that is worthy of investigation to address core fucosylated glycan intermediates involved in apoptosis and drug resistance. In this regard, reduced core fucosylation of TNF receptors may be mechanistically linked to decreased mitochondrial-dependent apoptosis because of the activation of the non-canonical NF-B pathway, as recently reported in osteosarcoma 75 . Therefore, targeting key (1,6)fucosylated proteins could strengthen the panoply of treatment alternatives for CRC and other neoplasias characterised by exacerbated core fucosylation 76,77 .…”
Section: Discussionmentioning
confidence: 52%
“…In addition, Lin et al demonstrated that fucosyltransferase 8 (FUT8) influences OS survival by regulating the core fucosylation levels of TNF receptors (TNFRs). Decreased fucosylation of TNFRs activates the non-canonical NF- B signaling pathway, ultimately reducing mitochondria-dependent apoptosis in OS cells [ 50 ]. The contradictory results regarding the expression of these TNFRSF1A genes may be related to tissue specificity and age range.…”
Section: Discussionmentioning
confidence: 99%
“…However, FUT8 was found to be expressed at lower levels in osteosarcoma, leading to lower core fucosylation levels of TNF receptors. Lower fucosylation of TNF receptors decreased mitochondria-dependent apoptosis by activating NF-κB2 signalling [ 37 ]. Interestingly, our study revealed that FUT8 was upregulated in OC tissues but was a good prognostic factor.…”
Section: Discussionmentioning
confidence: 99%